Evaluation of the efficacy of defluoration systems with absorption materials for water treatment in endemic fluorose areas: an integrative review (Research, Society and Development, 2020)
Fluoride is the 13th most abundant element in the world, with drinking water being the biggest contributor to its intake. Exposure to fluoride - in excessive conditions - causes toxicity and can manifest as dental fluorosis. Thus, defluoridation is a physical-chemical mechanism that reduces the concentration of fluoride in the water, as a way of preventing fluorosis. Therefore, the study aims to evaluate the efficacy of the systems of defluoridation with adsorption materials in endemic areas of fluorosis. For that, the utilization used, if of an integrative literature review, consisting of the steps of: elaboration of the guiding question, data collection, evaluation, analysis and interpretation of the presented data and presentation of the results. According to what was found, most of the studies verified the possibility of using bauxite and other materials for the water defluoridation, reaching the indication of the fluoride concentration recommended by the Consolidation Ordinance / MS nº5 / 2017, Annex XX. One of the most economical processes for removing fluoride from water for human consumption is adsorption, which also provides benefits for efficiency. Therefore, it is concluded that defluoridation systems for water treatment in endemic areas of fluorosis consist of highly effective elements for reducing the incidence of fluorosis disease.